Exports Cause Outward Foreign Direct Investment in Indian Pharmaceutical Industry?. (December 2017) - Suri, F. K.; Banerji, A.
This article discusses the relationship among exports, outward FDI and total sales of Indian pharmaceutical industry. Aim is to analyze a two-way causal relationship among exports and outward FDI from Indian pharmaceutical market to understand whether exports and outward FDI are supplementary or complementary in nature. The article also aims to analyze how exports and outward FDI are affected by the lagged year's values. The article illustrates the trend of exports and outward FDI from Indian pharmaceutical sector to draw an eclectic paradigm to study the impact of exports on outward FDI. A vector auto regression (VAR) model has been developed on exports and outward FDI, keeping total sales as exogenous variable using a lag of one and two years. The VAR model-substituted coefficients suggest that pharmaceutical exports are directly affected by last year Pharma OFDI. It was found that in context of Indian pharmaceutical sector, exports cause outward FDI and in turn previous year's outward FDI has a direct impact on current year's exports.